(untitled) - Scheidel, Jeff (New York, 2010)
The book begins by defining identity and access management and explaining how to assess an organization's need for an IAM framework. This Oracle Press guide then teaches you, set by step, how to determine the functionality required by your organization, design a framework, and implement the actual features and functions needed for supporting true business requirements. Oracle Identity and Access Management Suite provides a comprehensive solution to the entirety of an organization’s identity and security requirements. This book fully explains how to implement all of the suite’s components and touches on the infrastructure pieces that provide a foundation for the suite, as well as aid in governing the components and tying identity to application security.
Keywords: Computers,Máy tính; Access control.,Kiểm soát truy cập